Evaluation of Readiness of Emergency Response Facilities and Means in Industrial Areas: Literatur Review - Harahap, Muhammad Wandi; Panjaitan, Juhri; Andrika, Nuansah; Hasibuan, Abdurrozzaq (Universitas Ibn Khaldun, 2025)
In the industrial world, the risk of disasters such as fires, explosions, or workplace accidents can arise at any time, so preparation to deal with emergency situations is very important. Emergency preparedness involves a variety of elements, from physical infrastructure and equipment to training and awareness-raising of human resources. This research applies library research or literature study. To obtain data for literacy studies, books, research journals published locally and internationally, scientific articles, and research conducted by others can be referred to. A literature review is an overview of the literature related to a theme. It provides information on recent advances in the field. Based on the analysis of eight journals on the readiness of facilities and emergency response systems in industrial areas, it can be concluded that, although many industries have made significant efforts to improve their emergency response systems, there are still several challenges that need to be addressed. Some key findings from this research include: Compliance with Standards, Many facilities show a high level of compliance with safety standards, but there are still elements that need improvement. Routine assessments are crucial to ensure that every element of the disaster response system functions well. The significance of training, awareness, and understanding of emergency response procedures among employees is very important.